PUMA mediates the apoptotic response to p53 in colorectal cancer cells - Yu, Jian (The National Academy of Sciences, 2003)
Although several genes that might mediate p53-induced apoptosis have been proposed, none have previously been shown to play an essential role in this process through a rigorous gene disruption approach. We used a gene-targeting approach to evaluate p53-mediated death in human colorectal cancer cells. Expression of p53 in these cells induces growth arrest through transcriptional activation of the cyclin-dependent kinase inhibitor p21. If p21 is disrupted via gene targeting, the cells die through apoptosis. If the PUMA gene is also disrupted in such cells, apoptosis is prevented. The effects of PUMA on apoptosis were observed after exogenous overexpression of p53 as well as after exposure to hypoxia, a physiologic activator of p53, and DNA damage. The PUMA protein interacts with Bcl-X(L) and promotes mitochondrial translocation and multimerization of Bax. Accordingly, genetic disruption of BAX makes cells resistant to the apoptosis resulting from PUMA expression. These results suggest that the balance between PUMA and p21 is pivotal in determining the responses to p53 activation and provide a model for understanding the basis of p53 mutations in human cancer.